Traumatic dentoalveolar fracture in a dog—An unusual and misdiagnosed injury - Fracascio, Sabrina [UNESP]; Pignone, Víviam Nunes; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Rahal, Sheila Canevese [UNESP]; Melchert, Alessandra [UNESP] (Wiley, 2024)
The lateral luxation of a tooth is a traumatic dentoalveolar injury, which causes partial or complete tooth displacement and periodontal damage. We report a female mixed-breed dog referred to the dentistry service with a lateral luxation of the maxillary left canine tooth due to a trauma-related alveolar bone fracture. This unusual lesion is often misdiagnosed as a tooth fracture and potentially treated with extraction. Another major challenge is the need for emergency treatment since time decreases the number of periodontal ligament cells and hinders the pulp vascular supply. Without endodontic treatment, it may progress to pulp necrosis, root reabsorption and tooth loss. Instead of the classical treatment with a ligature wire, we performed a splint with acrylic resin, followed by root canal therapy and postoperative care. This technique was successful and spared the tooth, which remained structurally and periodontally sound and functional over 2 years of follow-up.